PENGARUH PEMANASAN TERHADAP PERKECAMBAHAN DAN KESEHATAN BENIH KEDELAI (Glycine max (L.) Merrill) - , MEILAN SITUMEANG ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Certified soybean seed which were circulated in the market only guarantee the value of germination and purity of the seed. Seedâs healthy test was not included in certification test. The infected seed could influence the plantâs growth and become the source of infection in the field. Seed treatment has become a part of practice in order to maintain the quality of the seed. Seed treatment is used to remove the source of seed infection, protects the seeds from pathogens and pests, and improve seed germination. This research aimed to know the effect of heat treatment to germination and health of the seed, and to determine the proper heat treatment to eliminate pathogen without decreasing the germination of seed. This research was conducted by hot water treatment and dry heat treatment of soybean seed at different temperature and time. Both of the treatment were observed separately. This research used a 3x3 factorial design. The first factor was temperature and the second one was the length of time. Hot water treatment was done at various temperature of 45, 55, and 65 Â° C with length of time 10, 20, and 30 minutes. Dry heat treatment was also done at three different temperatures at 50, 60, and 70 Â° C with the length of time 1,2, and 3 hours. Control treatment was done by planting seeds on top of filter paper in petridish and directly in soil without heat treatment. Each treatment was replied 4 times. To compare the hot water treatment and the dry heat treatment with control, T test is used. Hot water treatment at 45 Â° C for 10 minutes is the appropriate heat treatment due to the short time of this treatment could eliminate 9 types of fungal colonies which were grown without reducing germination of the seed. The results showed that the heat treatment at 60-70 Â° C can decrease germination of the seed.